The Perception of Trusmi Cirebon Batik Products on The Role of Sharia Banking Micro, Small, and Medium Industry - Huuruniin Huuruniin; Asyari Hasan (MediaTrend, 2022)
The presence of Islamic banks is expected to have an extraordinary impact on the growth of the real sector, especially Micro, Small and Medium Enterprises. This study aims to analyze the Perceptions of Micro, Small, and Medium Enterprises of Trusmi Cirebon Batik Products on the Role of Islamic Banking. This research is descriptive qualitative, a case study of Batik Trusmi Cirebon. The findings of this study, that the perception of Batik Trusmi Cirebon's Micro, Small and Medium Enterprise's home industry on the role of Islamic banking is still very minimal, and product socialization from Islamic banks are still low, so Batik Trusmi Micro, Small and Medium Enterprises are not interested in making loans or financing at banks. Islam. Some of the factors that influence this condition include Islamic banks whose procedures are considered complicated to understand, unfamiliar product terms, uncertainty, and fear of financing in Islamic banks. The mentoring program also really needs to be carried out by Islamic banks. By providing mentoring programs, people will automatically get to know Islamic banks without having to carry out socialization which is sometimes less effective.